2018
DOI: 10.4178/epih.e2018010
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities and difficulties to access to healthcare services among Canadian children with neurodevelopmental disorders and disabilities

Abstract: OBJECTIVESThe aims of this study were to identify the associations of levels of severity of neurodevelopmental disorders and disabilities (NDD/D) in children with their household socioeconomic status (SES) and their frequency of visits to a healthcare provider, and to examine how the severity of disability varied with these determinants among NDD/D subgroups, in order to inform possible social policy changes and to improve access to the healthcare system.METHODSData from the 2006 Participation and Activity Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This is an important problem since women and couples who would have the fewest resources to cope with costs of care for an affected child are least likely to access RCS testing. 17 Although childhood-onset recessive conditions individually are rare, international pan-ethnic studies have reported that as many as one-third of individuals test positive for at least one condition. 18 A similar study from Australia, reporting the results of 12 000 limited RCS (CF, SMA, and FXS only) found that one in 20 individuals tested was found to be a carrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important problem since women and couples who would have the fewest resources to cope with costs of care for an affected child are least likely to access RCS testing. 17 Although childhood-onset recessive conditions individually are rare, international pan-ethnic studies have reported that as many as one-third of individuals test positive for at least one condition. 18 A similar study from Australia, reporting the results of 12 000 limited RCS (CF, SMA, and FXS only) found that one in 20 individuals tested was found to be a carrier.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that there is a steep socioeconomic gradient in uptake of RCS is striking: it seems likely there is a financial disincentive for women in more disadvantaged socioeconomic circumstances. This is an important problem since women and couples who would have the fewest resources to cope with costs of care for an affected child are least likely to access RCS testing 17 …”
Section: Discussionmentioning
confidence: 99%
“…Caregivers encounter significant challenges with accessing information and services, experience a lack of communication and coordination within and across agencies, and perceive the responsibility to coordinate their child’s services as overwhelming [ 7 – 9 ]. These experiences negatively impact family quality of life [ 10 ] and family burden [ 11 ], and those of low socioeconomic status [ 12 , 13 ] or who are immigrants [ 14 , 15 ] are further at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Although family-centered care is widely adopted to guide health and supportive care in many circumstances (Åstedt-Kurki, 2010; Foster et al., 2013; Kaakinen et al., 2018), additional efforts towards its integration can enhance care and support for children and their families. Advocacy for family-centred care and identification of strategies to support coping and well-being are crucial because some parents struggle to clearly identify and prioritize their needs, and social inequities can impose barriers to accessing essential care and support (Raouafi et al., 2018). In conjunction with interprofessional teams, social workers are optimally positioned to provide and advocate for holistic care for families through their capacity to foster collaboration, therapeutic communication, and mobilize supportive care resources and interventions.…”
Section: Introductionmentioning
confidence: 99%